Schwann Cell Contact Guidance versus Boundary Interaction in Functional Wound Healing along Nano and Microstructured Membranes. Issue 12 (22nd June 2015) - Tonazzini, Ilaria; Jacchetti, Emanuela; Meucci, Sandro; Beltram, Fabio; Cecchini, Marco
<x xml:space="preserve">Abstract</x> Peripheral nerve transection is often encountered after trauma and can lead to long‐term/permanent loss of sensor/motor functionality. Here, the effect of pure contact interaction of nano/microgrooved substrates on Schwann cells (SCs) is studied in view of their possible use for nerve‐repair applications. Elastomeric gratings (GRs; i.e., alternating lines of ridges and grooves) are developed with different lateral periods (1–20 μm) and depths (0.3–2.5 μm), leading to two distinct cell–material interaction regimes: contact guidance (grating period < cell body diameter) and boundary guidance (grating period ≥ cell body diameter). Here, it is shown that boundary guidance leads to the best single‐cell polarization, actin organization, and single‐cell directional migration. Remarkably, contact guidance is instead more effective in driving collective SC migration and improves functional wound healing. It is also demonstrated that this behavior is linked to the properties of the SC monolayers on different GRs. SCs on large‐period GRs are characterized by N‐Cadherin downregulation and enhanced single‐cell scattering into the wound with respect to SCs on small‐period GRs, indicating a less compact monolayer characterized by looser cell–cell junctions in the boundary guidance regime. The present results provide information on the impact of specific submicrometer topographical elements on SC functional response, which can be exploited for nerve‐regeneration applications.